The teen's guide to social skills : practical advice for building empathy, self-esteem, & confidence - Fitzsimons, Kate (Rockridge Press, 2021)
Understanding and overcoming social awkwardness and anxiety for teens In social situations, it can be really confusing to figure out what to say or do-and when you're a teenager, it often feels impossible to get past the awkwardness. No matter why you struggle, you can build up your confidence with this guide to social skills for teens! With the help of real scenarios and easy-to-remember strategies, you'll learn to identify the causes of your social discomfort and improve how you deal with tricky situations. As you practice, you'll get better at handling emotions, reducing conflict, calming anxiety, and feeling comfortable.